Suicidal Ideation Among Wives of Former Prisoners of War: A Longitudinal Dyadic Study. Issue 2 (2nd April 2016) - Zerach, Gadi; Levi-Belz, Yossi; Michelson, Menucha; Solomon, Zahava
Abstract : Objectives : The associations between posttraumatic stress disorder (PTSD) and suicidal ideation (SI) among ex-prisoners of war (ex-POWs) has recently been exemplified. Several studies have revealed the toll of war captivity in the secondary traumatization (ST) of ex-POWs' wives. This study aimed to assess SI among ex-POWs' wives and the longitudinal associations between their husbands' PTSD and their own ST. Method : A sample of 233 Israeli couples (142 ex-POW couples and a comparison group of 91 veteran couples) completed self-report measures of PTSD symptoms, SI, and depression at two time points: T1 (2003) and T2 (2008), 30 and 37 years after the 1973 Yom Kippur War. Results : Among control wives, although not among ex-POWs' wives, the more ST symptoms they reported, the higher their level of SI. Furthermore, for both research groups, husbands' PTSD and wives' ST were positively associated with their own levels of SI, respectively. Autoregressive cross-legged (ARCL) analysis demonstrated that SI at T1 predicted ST at T2 among control wives but not among ex-POWs' wives. Surprisingly, an actor-partner interdependence modeling (APIM) analysis revealed, only among ex-POWs' couples, that the more the husbands suffered from PTSD and SI, the more moderate the increase of the wives' SI was between T1 and T2, thus, leading to better outcomes in terms of the wives' SI. Conclusions : Ex-POWs' posttraumatic distress is longitudinally related to their spouses' ST and SI. Clinical implications of these findings of the relations between captivity trauma and suicidality for veteran couples are discussed.